Exogenous gonadotropin releasing hormone (GnRH) modulates scrotal and testicular biometrics, libido, endocrinological and heamatological profiles in Ganjam goat under humid tropical coastal ecosystem of Odisha - Jibanjyoti Nayak; Anil Kumar Nahak; Purna Chandra Mishra; Dillip Kumar Karna; Chinmoy Mishra; Perumal Ponraj (Asian Pacific Journal of Reproduction, 2022)
Objective: To assess the effect of exogenous gonadotropin releasing hormone (GnRH) in libido, scrotal and testicular biometrics, endocrinological and heamatological profiles of Ganjam goat buck during winter and pre-monsoon seasons. Methods: Forty eight healty Ganjam goat bucks of 3-4 years old were equally divided into the control and treatment groups. The control group received distilled water as placebo, while the treatment group received GnRH injection (4 μg Buserelin acetate/mL) once a week for four months. Body weight, scrotal circumference and testicular parameters (testicular volume, testicular weight and testis index), endocrinological profiles [follicle stimulating hormone (FSH), luteinizing hormone (LH), and testosterone], sex behavioural profiles (libido score, mating ability score, and sex behavioural score) and heamatological profiles (red blood cells, white blood cells, haemoglobin, and packed cell volume) were estimated. Results: The libido, scrotal and testicular biometrics, and endocrinological profiles significantly differed between the control and GnRH-treated bucks within and between the seasons within the two groups (P<0.05). Body weight, scrotal circumference, testicular volume, testicular weight, testis index, FSH, LH, testosterone, libido score, mating ability score, sex behavioural score, red blood cells, haemoglobin and packed cell volume were significantly higher in the GnRH-treated bucks compared to the control bucks in pre-monsoon and winter seasons (P<0.05). Body weight, scrotal circumference, testicular volume, testicular weight, testis index, FSH, LH, testosterone, libido score, mating ability score, sex behavioural score, red blood cell counts (in treatment), and haemoglobin were significantly higher in pre-monsoon compared to winter season in the experimental groups (P<0.05). The white blood cell counts neither differed between seasons nor between the two groups. Conclusions: Exogenous GnRH supplementation and pre-monsoon season have higher beneficial effects in improvement of endocrinological profiles with cascading beneficial effects on scrotal circumference, testicular volume, testicular weight, and sex behavioural profiles, which in turn will improve the sperm production and its cryo-survivability and fertility rate in Ganjam goat.